Transcriptomes and Proteomes Define Gene Expression Progression in Pre-meiotic Maize Anthers. Issue 6 (1st June 2014) - Zhang, Han; Egger, Rachel L; Kelliher, Timothy; Morrow, Darren; Fernandes, John; Nan, Guo-Ling; Walbot, Virginia
Abstract: Plants lack a germ line; consequently, during reproduction adult somatic cells within flowers must switch from mitotic proliferation to meiosis. In maize ( Zea mays L.) anthers, hypoxic conditions in the developing tassel trigger pre-meiotic competence in the column of pluripotent progenitor cells in the center of anther lobes, and within 24 hr these newly specified germinal cells have patterned their surrounding neighbors to differentiate as the first somatic niche cells. Transcriptomes were analyzed by microarray hybridization in carefully staged whole anthers during initial specification events, after the separation of germinal and somatic lineages, during the subsequent rapid mitotic proliferation phase, and during final pre-meiotic germinal and somatic cell differentiation. Maize anthers exhibit a highly complex transcriptome constituting nearly three-quarters of annotated maize genes, and expression patterns are dynamic. Laser microdissection was applied to begin assigning transcripts to tissue and cell types and for comparison to transcriptomes of mutants defective in cell fate specification. Whole anther proteomes were analyzed at three developmental stages by mass spectrometric peptide sequencing using size-fractionated proteins to evaluate the timing of protein accumulation relative to transcript abundance. New insights include early and sustained expression of meiosis-associated genes (77.5% of well-annotated meiosis genes are constitutively active in 0.15 mm anthers), an extremely large change in transcript abundances and types a few days before meiosis (including a class of 1340 transcripts absent specifically at 0.4 mm), and the relative disparity between transcript abundance and protein abundance at any one developmental stage (based on 1303 protein-to-transcript comparisons).